BATAVIA IN THE19th CENTURY: A RUSSIAN DIPLOMAT'S CRITICISM OF THE CAPITAL SOCIETY AND THE COLONIAL SYSTEM OF THE DUTCH EAST INDIES - Fahrurodji, Ahmad (International Review of Humanities Studies, 2024)
ABSTRACT This article analyzes the traces of diplomatic relations between the Russian Empire and the Dutch East Indies in the late 19th century. The views and criticisms of the Russian Consul in Batavia became one of the important milestones of cultural relations between the two nations in the future. This research is a cultural history research using historical research method and structural approach. The documents used are diplomatic reports that have been published in the original language (Russian). By using the theory of hermeneutics, this article aims to see how Batavia and the people in it interacted and acted from a Russian perspective. The article sets the following objectives: (1) to provide an overview of Batavia and its society in the colonial era from a Russian perspective. (2) to analyze Bakunin's views on social structure and the lives and social strata created through the policies of the colonial government. From the data analysis and findings, this article concludes with Bakunin's criticism of the life of the European society in Batavia and the colonial system that had placed the indigenous people in the lowest class position.